A guide to caring for patients who identify as transgender and gender diverse in the emergency department - Logan Jardine; Courtney Edwards; Hannah Janeway; Chance Krempasky; Wendy Macias‐Konstantopoulos; Paula Whiteman; Antony Hsu (Journal of the American College of Emergency Physicians Open)
Abstract Through a review of current research, standards of care, and best practices, this paper serves as a resource for emergency physicians (EPs) caring for persons who identify as transgender and gender diverse (T/GD) in the emergency department (ED). Both patient‐ and physician‐based research have identified existent potential knowledge gaps for EPs caring for T/GD in the ED. T/GD have negative experiences related to their gender identity when seeking emergency medical care and may even delay emergency care for fear of discrimination. Through the lens of cultural humility, this paper aims to address potential knowledge gaps for EPs, identify and reduce barriers to care, highlight gender‐affirming hospital policies and protocols, and improve the care and experience of T/GD in the ED.